(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Mr. Gourab Saha, Associate Professor, Department of Pharmaceutics, College of Pharmaceutical Sciences, Berhampur, Mohada, Odisha, India Abstract Special populations require modified pharmaceutical care approaches due to physiological differences affecting drug response, disposition, and safety profiles. Pediatric pharmacy addresses age-dependent variations across neonatal, infant, child, and adolescent groups, with developmental pharmacokinetic changes affecting absorption, distribution, metabolism, and excretion requiring weight-based or body surface area calculations, specialized formulations addressing swallowing difficulties, and particular vigilance for medications lacking pediatric labeling or safety data. Geriatric pharmacy focuses on multimorbidity, polypharmacy, and age-related physiological changes including reduced renal function, altered body composition, and diminished homeostatic mechanisms, necessitating deprescribing approaches, fall risk assessment, anticholinergic burden evaluation, and medication regimen simplification to enhance adherence and minimize adverse effects. Pregnancy and lactation considerations balance maternal benefit against fetal or infant risk using classification systems that evaluate reproductive toxicity and transplacental or breast milk transfer, with recommendations varying by trimester, condition severity, and alternative therapy availability. Renal and hepatic impairment significantly alter drug clearance pathways, requiring systematic dosage adjustments based on quantitative organ function assessment, with kidney dysfunction necessitating modifications for renally eliminated medications based on creatinine clearance calculations, and liver impairment affecting highly extracted drugs through altered metabolism and protein binding, requiring Child-Pugh classification-guided interventions. Therapeutic approaches across these populations emphasize individualized therapy, heightened monitoring, and interdisciplinary collaboration to optimize medication effectiveness while minimizing iatrogenic harm Keywords: Pharmacokinetics; Physiological alterations; Dose individualization; Organ dysfunction; Vulnerability VIEW PDF